Determinants Moderators of Financial Distress: An Evidence Affiliation Group and Political Connection - Rony Wardhana; Muslich Anshori; Heru Tjaraka (AKRUAL: JURNAL AKUNTANSI, 2022)
There is a theoretical gap in the research during the research period, so it is necessary to reconcile the findings, which is expected to be useful for all parties, academics, practitioners and related companies. The analysis used in this research is the Smart PLS tool. The population in this study are all manufacturing industrial companies listed on the Indonesia Stock Exchange for the 2017-2020 period. The sample of this study amounted to 144 companies. Tax aggressiveness shows results that do not affect the capital structure of manufacturing companies. Investment decisions affect the increase in capital structure in manufacturing companies. The capital structure shows a strong influence on financial distress in manufacturing companies. The results of the indirect effect test explain that tax aggressiveness has no significant effect on financial distress through capital structure. The results of the indirect effect test explain the substantial impact of investment decisions on financial distress through capital structure. The results of the moderating effect test show that the capital structure has no significant effect on financial distress with group affiliation moderation. The results of the moderating effect test explain the significant effect of capital structure on financial distress by moderating political connections.